Collaborative Caching for D2D Content Sharing in 5G - Abdelsalam, Ansam Elfadil Kamel (2021)
A Master of Science thesis in Computer Engineering by Ansam Elfadil Kamel Abdelsalam entitled, “Collaborative Caching for D2D Content Sharing in 5G”, submitted in May 2021. Thesis advisor is Dr. Rana E. Ahmed. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).